Meta-Analysis of the Impact of Domestic Violence (DV) on Children's Mental Health and Academic Achievement - Shofa, Ghefira Zairah; Sari, Syintia Puspita; Ingtyas, Fatma Tresno; Ginting, Laurena (CV. Tripe Konsultan, 2024)
Domestic Violence (DV) can damage the relationship between parents and children, negatively affecting children's mental health. This study analyzes the impact of DV on children's mental health through a meta-analysis of 15 national journals. The results show that children who are victims of DV often experience anxiety, depression, and difficulties in socializing and learning. The main psychological impacts are anxiety and depression, which can lower self-confidence and affect social relationships. Proper psychological intervention is necessary to reduce these negative effects.